The potential role of polyelectrolyte complex nanoparticles based on cashew gum, tripolyphosphate and chitosan for the loading of insulin - Bezerra, Janira M. N. A. (2021)
Polyelectrolytic complexation has stood out due to its application in the development of drug delivery systems using biopolymers as raw materials. The formation of complexes between cashew gum and chitosan can be intermediated by cross-links, mediated by the action of the sodium tripolyphosphate crosslinking agent. These polymers have been used in the nanotechnological development of formulations to protect peptide drugs, such as insulin, allowing their oral administration. In this work, we describe the development of polyelectrolytic complexes from cashew gum and chitosan as biopolymers for oral administration of insulin. The obtained complexes showed a mean particle size of 234 nm and polydispersity index of 0.2. The complexes were 234 nm in size, PDI 0.2, zeta potential 4.5 mV and 22% trapping. The obtained complexes demonstrated considerable and promising characteristics for use as oral insulin delivery systems.